SignAR: A Sign Language Translator Application With Augmented Reality - Soogund, Noor-Un-Nissah B.N; Joseph, Minnu Helen (Journal of Applied Technology and Innovation, 2019)
Various studies have shown that deaf/non-hearing students face challenges in reading comprehension mostly because they cannot develop a fluent system of communication required to become proficient readers. This can affect their communication skills, leading to an overall depressed academic achievement and social seclusion. This is where SignAR comes into play. SignAR will help deaf children learn English as well as sign language and hearing people can also use it to learn sign language. So, basically, once a word has been captured by the phone camera, the corresponding sign animation will be augmented on the user’s screen. By using SignAR, the deaf children will be able to learn English using Signs while hearing users will learn Signs using English. In this way, the communication barriers between the hearing and non-hearing will hopefully be greatly diminished.